The behavioural intention of mobile payment adoption in food service establishments among generation X - Muhamad Zuni, Zulaikha Che; Deraman, Fauziah; Abd. Hamid, Maisarah; Ismail, Noralisa (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study investigates a relationship between the behavioural intention of mobile payment adoption in food services establishments among Generation X in Dungun, Terengganu. Specifically, the research has examined the influence of three key factors, which are Performance Expectancy (PE), Effort Expectancy (EE), and Trust (TR), on the Behavioural Intention to adopt mobile payment technologies within the food service industry. The objectives of this study are to assess the relationship between Performance Expectancy (PE) and Behavioural Intention towards mobile payment adoption, to examine the relationship between Effort Expectancy (EE) and Behavioural Intention, and to observe the relationship between Trust (TR) and Behavioural Intention towards mobile payment adoption in food service establishments. A quantitative approach has been employed, with data collected through questionnaires administered to 378 respondents. The data have been analysed using IBM SPSS Version 29 to determine the extent to which PE, EE, and TR influence Generation X’s behavioural intention towards mobile payment adoption in food services. This study has provided insights into the factors that drive or hinder the adoption of mobile payment systems in the food service sector in Dungun, Terengganu, contributing to a theoretical and practical understanding of the mobile payment adoption behaviour. Based on the multiple linear regression analysis, this study has confirmed that Performance Expectancy, Effort Expectancy, and Trust have a positive relationship with Behavioural Intention.